Carbon Caps for European Cars. - Blau, J. (IEEE spectrum)
Nowadays, European automobiles generate about one-fifth of the European economy's total carbon dioxide emissions, compared with almost a third in the United States. This paper discusses how European car manufacturers intend to change that. To achieve this, the country has been told to reduce its annual carbon-emission level to 453 metric tons from the 482 proposed by politicians. And, in particular, the commission has pointed a finger at the country's powerful car-manufacturing sector, threatening to present automakers there and across the EU with a mandate to sell lower-emission vehicles. A commission proposal is now on the table that calls for a legally binding limit of 130 grams per kilometer for the average new car fleet built from 2012 onward. The plan for a mandatory cap comes after years of bickering over a voluntary limit, which the commission argues has failed